2020
DOI: 10.3390/educsci10060169
|View full text |Cite
|
Sign up to set email alerts
|

Venues for Analytical Reasoning Problems: How Children Produce Deductive Reasoning

Abstract: The research on deductive reasoning in mathematics education has been predominantly associated with the study of proof; consequently, there is a lack of studies on logical reasoning per se, especially with young children. Analytical reasoning problems are adequate tasks to engage the solver in deductive reasoning, as they require rule checking and option elimination, for which chains of inferences based on premises and rules are accomplished. Focusing on the solutions of children aged 10–12 to an analytical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Most studies in management have applied deductive reasoning in their research methodology. Deductive reasoning needs to contain a structure of analytical reasoning for the research to arrive at a consensus [81]. The process of deductive reasoning ensures that the hypotheses have to be clarified as soon as the objective is specified, and the validity of the theories or hypotheses inferred from such a process depends on the capacity of scholars to identify the different elements of the research process logically [82].…”
Section: Methodsmentioning
confidence: 99%
“…Most studies in management have applied deductive reasoning in their research methodology. Deductive reasoning needs to contain a structure of analytical reasoning for the research to arrive at a consensus [81]. The process of deductive reasoning ensures that the hypotheses have to be clarified as soon as the objective is specified, and the validity of the theories or hypotheses inferred from such a process depends on the capacity of scholars to identify the different elements of the research process logically [82].…”
Section: Methodsmentioning
confidence: 99%
“…In other words, when students worked on assignments monitored by lecturers online at LMS, students felt the presence of lecturers. Many relevant studies stated that deductive thinking skills required continuous practice (Eglington & Kang, 2018;Carriera, Amando, & Jacinto, 2020). This study portrayed that tracing learning resources, making presentation files, and discussing them facilitated the students a lot in training their critical thinking.…”
Section: Resultsmentioning
confidence: 91%
“…Studies on deductive reasoning in early childhood have highlighted the importance of this cognitive skill for various aspects of a child’s development. For example, proficiency in deductive reasoning has been linked to improved problem-solving capabilities ( Józsa et al 2023a ), mathematical understanding ( Mohammad and Albaqawi 2023 ), and analytical reasoning skills ( Carreira et al 2020 ). Moreover, it plays a crucial role in academic achievement, particularly in subjects that require logical thinking and problem-solving, such as mathematics and science ( Csapó et al 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the realm of elementary mathematics education, one study ( Carreira et al 2020 ) evaluates deductive reasoning through the introduction of a specific analytical reasoning problem. The finding showed that engaging children in reasonably intricate analytical reasoning exercises can assist in supporting a wide range of deductive reasoning development among young children.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation